Validitas LKPD Fisika SMA Menggunakan Model Problem Based Learning Berbasis Teknologi Digital - Riti Desmiwati; Ratnawulan Ratnawulan; Yulkifli Yulkifli (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
One effort that can be done by teachers to improve the competence of students was to develop of Student Worksheet (LKPD). LKPD was said to be qualified if it has valid criteria. Valid means the developed product can be used to measure what should be measured. Validity of LKPD was assessed by experts in the field. The purpose of this study was to determine the validity of LKPD experimentphysics oriented by problem based learning models be used tools practicum based on digital technology. The methode of this study was descrptive methode. The research instrument used was validation sheet in the form of assessment questionnaire. Analysis of data used descriptive analysis. The validation result was obtained LKPD physics experiment oriented Problem Based Learning model with tools of practicum based on digital technology was valid criteria.